Learning support teacher competencies in dealing with digital learning units in Jordan - Hamadneh, Burhan Mahmoud; Malkawi, I’temad Khalid (Asian Journal of Contemporary Education, 2025)
This study investigates the competencies of Learning Support Teachers (LSTs) in utilizing digital learning units and explores differences based on gender, academic qualifications, and years of experience. A descriptive survey method was used, with a sample of 114 male and female LSTs randomly selected from public schools in Irbid Governorate during the second semester of the 2024–2025 academic year. Data were collected through an electronic questionnaire comprising 32 items across four domains: (1) essential digital learning competencies, (2) management of digital systems and content, (3) use of social media to enhance interaction in digital environments, and (4) integration of digital learning to support instruction and problem-solving. Results indicate that LSTs possess a moderate level of competence in using digital learning units. Significant differences were found in favor of teachers with postgraduate degrees and those with less than ten years of experience. No significant differences emerged based on gender. The study recommends that the Ministry of Education enhance digital teaching competencies among LSTs, particularly in supporting students with disabilities.